Beyond Enrollment: Managing Student Recruitment Campaigns in Social Media as an Outcome of Learning - Taufikin Taufikin (Universitas Nurul Jadid, 2024)
Amid an increasingly intense digital landscape, student recruitment promotion in Islamic boarding schools often remains merely an administrative practice rather than a pedagogical space. This gap raises fundamental questions about the possibility of integrating social media into an authentic learning process. This study aims to examine the management of student recruitment promotion as an outcome of social media learning at PPATQ Raudlatul Falah Pati, using a qualitative case study approach and employing participatory observation, in-depth interviews, and digital content analysis. The research findings indicate that promotional activities have evolved into a dynamic learning practice. Students do not merely serve as the subjects of promotion but as active content creators who construct religious narratives, visual aesthetics, and institutional identity. This process integrates digital literacy with spiritual character development, resulting in content that is not merely communicative but also reflective and educational. On the other hand, this practice reveals a tension between educational ideals and the logic of digital visibility, which demands a balance between authenticity and representation. This study proposes the concept of pedagogical branding as an integration of learning, student participation, and value-based promotional strategies. These findings contribute to the development of social media theory in Islamic education and offer practical implications for the design of adaptive, participatory, and meaningful learning in the digital age.